How do you solve using gaussian elimination or gauss-jordan elimination, 3x + y + 2z = 3, 2x - 37 - z = -3, x + 2y + z = 4?

1 Answer
Jan 19, 2016

x = 617/276
y = -15/92
z = 577/276

Explanation:

I assume that there is a transcription error in the question and the second term in the second equation should actually be a y term.

3x + y + 2z = 3
2x - 37y - z = -3
x+2y+z = 4

Adding together the second and third equations gives us
3x -35y =1

Next, doubling the second equation and adding it to the first gives
7x -73y = -3

Solving these two equations gives 7*(3+35y)/3 -73y = -3
21+35y - 219y -= - 9
184y = -30
y = -15/92

:.3x = 1+35*15/92 = (92+525)/92 = 617/92
x = 617/276

Then z = 4 - 617/276 -2*(-15/92)
z = (1104 - 617 +90)/276 = 577/276